2022
DOI: 10.1093/molbev/msac259
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Mapping and Comparative Genomic Analysis Reveal the Gene Composition at theSandZSelf-incompatibility Loci in Grasses

Abstract: Self-incompatibility (SI) is a genetic mechanism of hermaphroditic plants to prevent inbreeding after self-pollination. Allogamous Poaceae species exhibit a unique gametophytic SI system controlled by two multi-allelic and independent loci, S and Z. Despite intense research efforts in the last decades, the genes that determine the initial recognition mechanism are yet to be identified. Here, we report the fine-mapping of the Z-locus in perennial ryegrass (Lolium perenne L.) and provide evidence that the pollen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The downstream reaction upon pollen–stigma interaction in grass appears to involve Ca 2+ signal transduction, protein phosphorylation, and proteolysis pathways ( Yang et al., 2008 ; Klaas et al., 2011 ; Chen et al., 2019b ). Comparative genomic analysis suggested a duplicated origin of the grass SI system owing to the similar gene composition and structure of the S- locus and Z -locus, and the high synteny between these two loci in the Poaceae tribe supported the hypothesis that grasses share the same SI determinants ( Rohner et al., 2023 ). Fine-mapping and comparative studies identified two DUF247 family genes ( SDUF247-I and SDUF247-II ) and an sS gene as the male and female determinants, respectively, at the S -locus ( Manzanares et al., 2016 ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 84%
See 2 more Smart Citations
“…The downstream reaction upon pollen–stigma interaction in grass appears to involve Ca 2+ signal transduction, protein phosphorylation, and proteolysis pathways ( Yang et al., 2008 ; Klaas et al., 2011 ; Chen et al., 2019b ). Comparative genomic analysis suggested a duplicated origin of the grass SI system owing to the similar gene composition and structure of the S- locus and Z -locus, and the high synteny between these two loci in the Poaceae tribe supported the hypothesis that grasses share the same SI determinants ( Rohner et al., 2023 ). Fine-mapping and comparative studies identified two DUF247 family genes ( SDUF247-I and SDUF247-II ) and an sS gene as the male and female determinants, respectively, at the S -locus ( Manzanares et al., 2016 ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 84%
“…The GSI system is controlled by two multiple-allelic loci, S and Z ( Li et al., 1997 ). Each locus contains two male and one female determinant, and SI occurs when the pollen S - and Z - genotypes are identical to the corresponding pistil genotypes ( Rohner et al., 2023 ). The downstream reaction upon pollen–stigma interaction in grass appears to involve Ca 2+ signal transduction, protein phosphorylation, and proteolysis pathways ( Yang et al., 2008 ; Klaas et al., 2011 ; Chen et al., 2019b ).…”
Section: Molecular Basis Of Self-pollen Rejection In Different Si Sys...mentioning
confidence: 99%
See 1 more Smart Citation
“…Self-incompatibility is a genetic mechanism of hermaphroditic plants to prevent inbreeding after selfpollination (Rohner et al, 2023) and has significant effects on population structure, potential diversification, and evolutionary consequences (Yang et al, 2008). This trait is frequently estimated as the seed set of randomly selected OP and SP panicles (Acuña et al, 2007(Acuña et al, , 2009Conde-Lozano et al, 2011;Hignight et al, 1991;Shafer et al, 2000).…”
Section: Crop Sciencementioning
confidence: 99%
“…The conservation of a single gene is striking, as to our knowledge all SI systems so far elucidated at the molecular level entail the action of at least two separate genes, determining the male and female specificities, respectively (Fujii et al 2016, Rohner et al 2023). These determinants vary greatly in the molecular functions they encode (Broz and Bedinger 2021) and in their level of repetition, with the male determination being, for example, spread across multiple tandemly duplicated paralogs in Solanaceae (Kubo et al 2015).…”
Section: Treatment With Gibberellin Disrupts the Pollen And Stigma Si...mentioning
confidence: 99%